Situational analysis of Laboratory Animal Sciences (LAS) status in Gulf Cooperation Council (GCC). (Journal of Laboratory Animal Science, 2024)
Laboratory Animal Sciences play a pivotal role in scientific research, significantly contributing to various fields such as  medicine, biology, and toxicology. This discipline is crucial in advancing scientific knowledge, improving healthcare  outcomes, and ensuring animals’ ethical and responsible use in research. Animal health is paramount in this field, yet it is  sometimes neglected during experimentation. To address this concern, many countries have developed their regulations  for animal welfare. Moreover, globally, the WOAH (World Organisation for Animal Health) has introduced guidelines  and regulations mandating research organizations to prioritize animal health. An international organization is ICLAS  (International Council for Laboratory Animal Science) which is dedicated to advancing laboratory animal science  worldwide, promoting the ethical use of animals in scientific research, and ensuring their welfare. In conjunction with  ICLAS, several other organizations share responsibilities for promoting good animal practices globally. This paper provides a comprehensive overview of the Laboratory Animal Sciences within the GCC countries. A brief  infrastructure detail that supports animal welfare and the significance of these facilities in facilitating cutting-edge re search is explored, alongside an analysis of the accreditation and management protocols crucial for their effective op - eration. Additionally, the paper scrutinizes the current laws and regulations governing laboratory animal welfare and  experimentation in the GCC region. As a forward-looking contribution, the paper outlines prospective developments  and expansion opportunities for laboratory animal sciences in the GCC, aiming to propel scientific advancements in the region. This research provides a valuable resource for scientists, policymakers, and stakeholders invested in promoting  ethical and effective laboratory animal research practices in the Gulf region.
Keywords: Gulf Cooperation Council; Laboratory Animal Sciences; Animal Welfare